Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Classification and mechanisms of summer drought types in Eastern Northwest China - Bicheng Huang; Yue Zhang; Hongyan Shen; Rong Zhi; Tao Su; Zhonghua Qian; Yongping Wu (Atmospheric Research, 2026)

Seasonal hydrochemical variations of a regulated river in the North China Plain: mechanisms and implications for chemical weathering - Xi Yang; Tao-Tao Ji; Zhi-Yuan Zhang; Rong-Tao Ma; Xiao-Wei Jiang (Journal of Hydrology, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Granite weathering revealed by magnesium isotopes fractionation: Implications for the flux dynamics and global carbon sink - Kai Luo; Jin-Long Ma; Fang-Zhen Teng; Gang-Jian Wei; Guan-Hong Zhu; Jia-Rong Liu; Zhuo-Ying Zhang; Zhi-Bing Wang (Chemical Geology, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Formation, Potential, and Challenges of Marine-Continental Transitional Shale Gas in China - Caineng Zou; Dazhong Dong; Qin Zhang; Weiliang Kong; Wen Liu; Zhenyu Zhao; Zhi Yang; Qun Zhao; Rong Ding; Guangyin Cai; Tianquan Qu; Wanli Gao; et al. (Journal of Earth Science, 2026)

Guaianolide sesquiterpenoids from Chrysanthemum indicum L. alleviate rheumatoid arthritis by targeting of NLRP3 inflammasome pathway - Gui-Min Xue; Hao Feng; Dong-Rong Zhu; Xin-Xin Guo; Ding-Qiao Xu; Yan-Jun Sun; Yan-Le Zhi; Zhi-Qiang Zhang; Guo-Sheng Li; Fa-Wu Dong; Jin-Feng Xue (Phytochemistry, 2026)

Functional characterization of a canonical C-type lectin from Mytilus coruscus: Roles in innate immunity and feeding processes - Ying-rong Jin; Chuan-yue Chen; Ze-kai Wang; Pan Qin; Zhi Liao; Xiao-lin Zhang; Xiao-jun Yan (Fish & Shellfish Immunology, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Photoelectron-driven modulation of carbon metabolism enhances hydrogen production in a ZnIn2S4-Shewanella oneidensis biohybrid system - Xue-Meng Wang; Hao-Yu Li; Kai-Li Wang; Zhi-Xuan Zhang; Yu-Xin Cao; Ya-Lian Ma; Rong Chen (Bioresource Technology, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Design, synthesis, characterization and exploration of anti-HBV activity of matrine-adenine hybrids - Meng-Fan Xie; Zhou-Fei Zheng; Jing-Lei Wang; Rong-Tao Li; Zhi-Jun Zhang (Molecular Diversity, 2026)

Mitigating 2-MIB and odor-producing cyanobacteria in a shallow drinking-water reservoir using sponge‑iron-assisted water-lifting aeration - Fei Zhang; Rong Li; Hao mu; Yuhai Zhuo; Zhi Yang; Tinglin Huang; Nan Li (Journal of Water Process Engineering, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Dynamic responses and failure modes of ultra-high strength alkali-activated concrete slab under impact load - Haiyu He; Lihua Wu; Xudong Zhi; Feng Fan; Gang Ma; Rong Zhang (Engineering Structures, 2026)

Efficient floor response spectrum estimation via a condensation-based modal combination framework - Fengze Li; Xudong Zhi; Duozhi Wang; Nawawi Chouw; Rong Zhang; Feng Fan (Engineering Structures, 2026)

A CBAM-integrated deep convolutional neural network for weather radar echo correction to overcome terrain occlusion challenge - Hao Wang; Zhihao Liu; Fugui Zhang; Zhi Li; Qiangyu Zeng; Tiantian Yu; Rong Yang (Advances in Space Research, 2026)

Global patterns and soil controls governing terrestrial nitrogen cycling in response to experimental warming: A meta-analysis - Sen-Mao Zhang; Wan-Jia Hu; Xin-Rong Shi; Robert L. Kallenbach; Zhi-You Yuan (Soil Biology and Biochemistry, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Mediating role of metabolic dysfunction-associated fatty liver disease in the association between individual-level noise exposure and liver enzymes in Chinese automotive manufacturing workers - Sijia Ou; Jiaheng Yu; Zhaoqian Chen; Yanmei Ruan; Xing Rong; Zejin Ou; Yuxia Zhang; Haijuan Huang; Jiaxin Cui; Zhi Wang (International Archives of Occupational and Environmental Health, 2026)

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Herder cooperatives vs. independent herders in Inner Mongolia: A comparative analysis of multi-dimensional efficiency - Jiuzhou Jin; Ruiyao Zhang; Pengpeng Dou; Rong Zhi; Ping Li (Agricultural Systems, 2026)

Reducing the Discrepancy in Quantifying the Temperature Dependence of Global Wetland Methane Emission - Han Hu; Ke Xue; Yishen Sun; Qing Zhu; Hans K. Carlson; Ruiwen Hu; Rong‐Xi Tan; Chao Qian; Weigen Huang; Jizhong Zhou; Jingdong Mao; Thomas W. Crowther; et al. (Global Change Biology, 2026)
Understanding the apparent temperature dependence of wetland methane emissions ( E M ) is critical for predicting climate‐carbon feedbacks, yet current estimates remain constrained by observational limitations and methodological inconsistencies. The inherent biogeographic heterogeneity of wetland ecosystems combined with sparse, unevenly distributed flux measurements introduces substantial uncertainty in characterizing spatial patterns of E M . This knowledge gap impedes accurate projections of wetland methane contributions under climate warming scenarios. Here, we develop a framework that integrates mixed‐effects models with artificial intelligence techniques to resolve scale‐dependent patterns in methane emission thermodynamics across global wetlands. Our unified framework demonstrates that only 73.6% (5th–95th quantiles: 71.8%–75.4%) of the global wetland area conforms to classical Arrhenius‐type temperature dependence. This framework can predict 69.5% (67.9%–71.1%) of the global wetlands with high confidence using the Mahalanobis distance and area of applicability tests. We quantify the weighted mean E M across high‐confidence predictable areas of 0.694 eV, with latitudinal differentiation: tropical (0.634 eV), temperate (0.678 eV), and boreal (0.745 eV) wetlands exhibit progressively stronger temperature responses. Ignoring these biogeographic variations could result in underestimation of projected end‐century methane emissions by 4.2%–13.3% across selected socioeconomic pathway scenarios. Our study refined the temperature sensitivity parameter in coupled climate‐carbon cycle models, thereby enhancing predictive accuracy of future global warming trends and informing strategic responses to climate change mitigation.

Co-reduction of nitrogen and phosphorus fertilizer inputs reduced nutrient losses and maintained crop yield in a rice-oilseed rape rotation system - Haodong Zhang; Ning Su; Gongwen Luo; Zhi Peng; Xizhe Luo; Sihai Qin; Mengjiao Huang; Chang Tian; Xiangmin Rong; Guixian Xie; Jun Xie (Soil and Tillage Research, 2026)

Millennial rice cultivation shapes depth‑dependent organic carbon mineralization and microbial life strategies in saline paddy soils - Chaoyun Ying; Zhi Ma; Yue Li; Xuechi Rong; Ze Zhang; Guanjun Li; Shuang Wang; Tida Ge; Zhenke Zhu (Soil and Tillage Research, 2026)

Synchronously interfacial fire retardancy and mechanical strengthening of glass fiber nylon 6 by temperature-responsive coupling agent - Han Li; Zhi Li; Rong Kuai; Wei-Zheng Zhang; Yanhao Huang; Qing-Wen Zeng; Zhi Hu; De-Yi Wang (Chemical Engineering Journal, 2026)

Bioactive constituents from Salacia obovatilimba as potential in vitro hSGLT2 inhibitors - Zhi-Yong Jiang; Lin Chen; Hong-Xi Xie; Jun-Jie Hao; Rong Chen; Chun-Qiu Huang; Hong-Lei Zhang; Ai-Xue Zuo (Phytochemistry, 2025)

Bi-mediated Z-scheme heterojunction of carbon-rich BiO2-X /Carbon nitride: Enabling a sensitive photoelectrochemical aptasensor for diazinon detection - Quan Shen; Rong Zhi; Song Zhang; Yi Ding; Jing Huang; Yuqi Chen; Keqiang Xu; Pengcheng Yan; Henan Li (Journal of Environmental Chemical Engineering, 2025)

Arthroderma guizhouense sp. nov., a Novel Geophilic Species from Guizhou, China - Kai-Rong Wang; Heng Pan; Bing-Da Sun; Gang Tao; Zhi-Yuan Zhang (Mycopathologia, 2025)

Freshwater flux-induced salinity effect on ENSO in the tropical Pacific under global warming - Hai Zhi; Jiahao Chen; Rong-Hua Zhang; Minmin Wu; Jiaxiang Gao; Lu-Ying Yin (Climate Dynamics, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Copper-Induced Nephropathy: Clinical Characterization of 36 Cases and Comprehensive Literature Review - Yi-Ling Li; Jing Chen; Jin-Rong Zhang; Ting-Ting Zhou; Jian-chao Peng; Zhi-Xin Huang; Kang Nong; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Structural variation in the promoter region of DcSOC1d influences flowering behavior in carrot - Kai Zhang; Rong-Hua Wu; Yu-Min Zhang; Ai-Sheng Xiong; Zhi-Sheng Xu (Journal of Plant Physiology, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

O304 is a mitochondrial uncoupler which extends C. elegans lifespan and induces vasorelaxation of rat mesenteric arteries - Wen-Feng Li; Yi Zeng; Yi-Dan Zhang; Rong Zhang; Jing Lang; Wen-Jie Bu; Meng-Ke Zhao; Zhi-Jie Sun; De-Li Dong (Chemico-Biological Interactions, 2025)

Crystal facet optimization in cadmium sulfide/reduced graphene oxide-based photosynthetic biohybrid systems for enhanced light-driven biohydrogen production - Xue-Meng Wang; Zhi-Xuan Zhang; Lin Chen; Rong Chen; Wen-Wei Li (Bioresource Technology, 2025)

Summertime bottom marine heatwaves in the East China Sea driven by oceanic circulation - Jiaxiang Gao; Rong-Hua Zhang; Hai Zhi (Journal of Oceanology and Limnology, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Biogenic Cu2-xSe nanoparticles with vacancy engineering quickly upcycle cobalt from wastewater for photothermal antibacterial and desalination - Xue-Meng Wang; Zhi-Xuan Zhang; Yun-Jie Wang; Hao-Yu Li; Wen-Wei Li; Rong Chen (Water Research, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Weakening of Bomb Cyclones over the North Pacific in the Early 21st Century - Jiaxiang Gao; Rong-Hua Zhang; Hai Zhi (Advances in Atmospheric Sciences, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sophormodines A−C, three alkaloids with antiviral activities against the HBV from the seeds of the Tibetan medicine plant Sophora moorcroftiana - Ting-Ting Liu; Meng-Fan Xie; Qing-Qing Yang; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

The application of nutrients in enhancing drought tolerance of secretohalophyte Atriplex canescens in the desert regions of Northwest China - Jian-jun Kang; Wen-zhi Zhao; Zhi-bin He; Bing Liu; Rong Yang; Hai Zhou; Dong-Mei Zhang (Plant and Soil, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Extraction of hydroxy safflower yellow A and anhydroxysafflor yellow B from safflower florets using natural deep eutectic solvents: Optimization, biological activity and molecular docking - Chun-Ying Wu; Bao-Rong Wang; Si-Yi Han; Ying-Hua Zhang; Zhi-Shen Mu (Food Bioscience, 2025)

Seasonal variations in marine heatwaves and their underlying mechanisms in the East China Sea - Jiaxiang Gao; Rong-Hua Zhang; Hai Zhi (Acta Oceanologica Sinica, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

A new sesquiterpene from endophytic fungus Colletotrichum sp. B-89 - Ke-tao Zhang; Bing Zhang; Zhi-pu Huang; Yu-xiao Xu; Xiao-rong Xu; Si-heng Li; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Experimental study on the coupled structure-isolated equipment system under near-fault pulse-like ground motions - Xudong Zhi; Kaiyuan Zhang; Feng Fan; Rong Zhang; Fengze Li (Engineering Structures, 2025)

Vanillic acid ameliorates collagen-induced arthritis by suppressing the inflammation response via inhibition of the MAPK and NF-κB signaling pathways - Yu Zhou; Pengfei Li; Zhongwen Zhi; Rong Chen; Chenghai Li; Chunbing Zhang (Inflammopharmacology, 2025)

Isolation, characterization and biological activities of phenolics from the roots bark of Morus alba - Min Tan; Xiao-Cong Liu; Dan Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Upper ocean salinity and temperature changes and their contributions to the stratification in the tropical Pacific under global warming - Hai Zhi; Rong-Hua Zhang; Meng Dong; Minmin Wu (Climate Dynamics, 2025)

Experimental and numerical study of light, fragile vent covers under vented gas explosions - Baicheng Zhou; Xudong Zhi; Yuhuan Song; Zhan Li; Feng Fan; Rong Zhang (Engineering Structures, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Precipitation patterns strongly affect vertical migration and methylation of mercury in legacy contaminated sites - Xujun Liang; Zhi-Cheng Hu; Yu-Rong Liu; Cunbin Gao; Yi Zhang; Yun-Yun Hao; Lijie Zhang; Jiating Zhao; Lizhong Zhu (Water Research, 2024)

Quantitative mechanisms for the Cd2+ adsorption increased by sewage-sludge biochar but decreased by rice-straw biochar after melamine modification - Zi-Xuan Yin; Yun-Yi Zhang; Jia-Xin Liu; Fei Huang; Qian-Jun Liu; Ming-Zhi Huang; Rong-Bo Xiao; Guo-Yi Gao; Tian-Zhen Lan; Xiao Zhou (Journal of Environmental Chemical Engineering, 2024)

Research advances in technologies and mechanisms to regulate vinegar flavor - Zhankai Zhang; Zhi-hong Zhang; Ronghai He; Guozhong Zhao; Yongjian Yu; Rong Zhang; Xianli Gao (Food Chemistry, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Structurally diverse diterpenoids from the leaves of Croton mangelong and their anti-diabetic activity - Zhi-Yong Jiang; Qi Niu; Hao-Xin Wang; Hao-Nan Xu; Hong-Xi Xie; Lin Chen; Rong Chen; Hong-Lei Zhang; Lu Gao; Ai-Xue Zuo; Hong-Ping He (Phytochemistry, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Versatile room temperature phosphorescence polymer with luminophore content as low as 0.05 wt% - Wen Wen Deng; Ze Ping Zhang; Min Zhi Rong; Ming Qiu Zhang (Chemical Engineering Journal, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Synergistic interdecadal effects of the North Pacific and North Atlantic SST on precipitation over eastern China as revealed in the ECHAM5 simulations - Minmin Wu; Rong-Hua Zhang; Hai Zhi; Junya Hu (Climate Dynamics, 2024)

Assessment of the hormesis effect and toxic damage of short-term low-dose aflatoxin B1 in grass carp (Ctenopharyngodon idellus) - Jin-long Li; Jia-rong Guo; Pei Wang; Jun-zhi Zhang; Zhi-gang He; Jin-long Wang; Yi Hu (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the hormesis and toxicity of short-term low-dose aflatoxin B1 in grass carp ( Ctenopharyngodon idellus ). Triplicate isonitrogenous and isocaloric aflatoxin B1 diets—CD (control, 0 ug/kg), D1 (20 ug/kg), and D2 (500 ug/kg)—were prepared and fed to grass carp with an initial mean body weight of (15.2 ± 0.1) g for 56 days. The results showed that the weight gain rate and specific growth rate of grass carp fed diet D2 were significantly higher, and the feed coefficient and crude fat content of the whole body were significantly lower ( P < 0.05) compared with those fed diet CD. Serum superoxide dismutase content of grass carp fed D1 diet increased significantly ( P < 0.05) with an increasing dose of aflatoxin B1, but when the dose reached 500 ug/kg (D2), serum superoxide dismutase, complement C3, and immunoglobulin M of grass carp decreased significantly ( P < 0.05), while malondialdehyde increased significantly ( P < 0.05). After short-term feeding of aflatoxin B1-containing diets (D1 and D2), liver body index, visceral body index, serum total cholesterol, triglyceride, and urea nitrogen content of grass carp increased significantly ( P < 0.05), total bile acid secretion decreased significantly ( P < 0.05), and structural damages such as increase in vacuoles, organizational structure loosening, and nucleus translocation were observed in the liver. Meanwhile, liver function indexes such as serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase increased significantly with the increase of aflatoxin B1 dose ( P < 0.05). In addition, the height of intestinal villi, crypt depth, villus–crypt ratio, and tubular cell number, as well as the content of trypsin and lipase activities in the intestine of grass carp in the D2 group, were significantly higher than those in the CD group ( P < 0.05). In conclusion, after a short-term intake of low doses of aflatoxin B1 (≤500 ug/kg), the toxicological damage of aflatoxin B1 was pronounced, although it produced a certain degree of hormesis on the growth performance and intestinal structure and function of grass carp. At a dose of 20 ug/kg, the non-specific immune system and liver structure and function of grass carp showed obvious toxic damage.

Composition of Sphagnum palustre L. extracts using different extraction methods - Zhi Wu; Zheng-Yi Hong; Yang Xu; Dai-Rong Wang; Qing-Bin Han; Ping Liu; Xiao-Rong Liu; Lan-Yue Zhang (Natural Product Research, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

FOXP4-AS1 promotes CD8+ T cell exhaustion and esophageal cancer immune escape through USP10-stabilized PD-L1 - Guo-yi Shen; Yi Zhang; Rong-zhi Huang; Zhi-yong Huang; Le-yi Yang; Ding-zhu Chen; Shao-bin Yang (Immunologic Research, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Salinity effect-induced ENSO amplitude modulation in association with the interdecadal Pacific Oscillation - Hai Zhi; Xiaokun Wang; Rong-Hua Zhang; Pengfei Lin; Jifeng Qi (Journal of Oceanology and Limnology, 2024)

Intestinal microbiota via NLRP3 inflammasome dependent neuronal pyroptosis mediates anxiety-like behaviour in mice exposed to 3.5 GHz radiofrequency radiation - Gui-qiang Zhou; Xing Wang; Peng Gao; Tong-zhou Qin; Ling Guo; Zhao-wen Zhang; Zhi-fei Huang; Jia-jin Lin; Yun-tao Jing; Hao-nan Wang; Chun-ping Wang; Gui-rong Ding (Science of The Total Environment, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Index construction and real-time hazard assessment of rice sterile-type chilling injury process in Northeast China - Bilige Sudu; Kaiwei Li; Suri Guga; Teri Gele; Feng Zhi; Ying Guo; Sicheng Wei; Guangzhi Rong; Yongbin Bao; Xingpeng Liu; Jiquan Zhang (Agricultural and Forest Meteorology, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

Building a stable and robust anti-interference DNA dissipation system by eliminating the accumulation of systemic specified errors - Luojia Wang; Wang Luo; Zhi Weng; Zhongzhong Wang; You Wu; Rong Zhao; Xiaole Han; Xin Liu; Jianhong Zhang; Yujun Yang; Guoming Xie (Analytica Chimica Acta, 2024)

A new 1,4-benzoxazine derivative produced by endophytic Colletotrichum gloeosporioides B-142 - Bing Zhang; Zhi-pu Huang; Yu Si; Ke-tao Zhang; Xiao-rong Xu; Jian-hong Chen; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2024)

Recovery and genetic characterization of clinically-relevant ST2 carbapenem-resistant Acinetobacter baumannii isolates from untreated hospital sewage in Zhejiang Province, China - Danxia Gu; Yuchen Wu; Kaichao Chen; Yanyan Zhang; Xiaoyang Ju; Zelin Yan; Miaomiao Xie; Edward Wai Chi Chan; Sheng Chen; Zhi Ruan; Rong Zhang; Jun Zhang (Science of The Total Environment, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

High-throughput analytical methodology of monoalkyl phthalate esters and the composite risk assessment with their parent phthalate esters in aquatic organisms and seawater - Qiang-Qiang Shi; Feng Xu; Tao Shen; Rong-Rong Zhang; Hua Liu; Ming-Ze Chen; Ai-Li Sun; Ze-Ming Zhang; Xi-Zhi Shi (Journal of Hazardous Materials, 2024)

Potential Role of Bmal1 in Lipopolysaccharide-Induced Depression-Like Behavior and its Associated "Inflammatory Storm" - Dan-Dan Xu; Zhi-Qi Hou; Ya-Yun Xu; Jun Liang; Ye-Jun Gao; Chen Zhang; Fan Guo; Dan-Dan Huang; Jin-Fang Ge; Qing-Rong Xia (Journal of Neuroimmune Pharmacology, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)

Synergistic Interdecadal Evolution of Precipitation over Eastern China and the Pacific Decadal Oscillation during 1951–2015 - Minmin Wu; Rong-Hua Zhang; Junya Hu; Hai Zhi (Advances in Atmospheric Sciences, 2024)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

Serendipita indica is a biostimulant that improves tea growth at low P levels by modulating P acquisition and hormone levels - Zi-Yi Rong; Ze-Zhi Zhang; Mashael Daghash Alqahtani; Qiang-Sheng Wu; Xiu-Bing Gao (Rhizosphere, 2023)

Chemical constituents of the leaves of Coriaria nepalensis and their chemotaxonomic significance - Min Tan; Xiao-Lan Chen; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Mesoscopic measurement of damage and shear bands of granite residual soil using Micro-CT and digital volume correlation - Cheng-sheng Li; Bing-xin Zhang; Zhi-jun Liu; Ling-wei Kong; Rong-jun Shu (Journal of Mountain Science, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

A spheropolyhedral-based discrete element lattice Boltzmann method for simulation of non-spherical adhesive particulate flow - Ye-Cheng Qian; Rong-Rong Cai; Li-Zhi Zhang (Computer Physics Communications, 2023)

Insights into roles of triclosan in microalgal–bacterial symbiosis system treating wastewater - Cong-Cong Tang; Tian-Yang Wang; Rong Wang; Cristiano Varrone; Zixuan Gan; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Bioresource Technology, 2023)

Serum levels of IL-6/IL-10/GLDH may be early recognition markers of anti-tuberculosis drugs (ATB) -induced liver injury - Huai-Rong Xiang; Yun Li; Xuan Cheng; Bei He; Hua-Min Li; Qi-Zhi Zhang; Bin Wang; Wen-Xing Peng (Toxicology and Applied Pharmacology, 2023)

Fabrication of a novel antioxidant emulsifier through tuning the molecular interaction between soy protein isolates and young apple polyphenols - Zhi Chao Song; Huan Zhang; Peng Fei Niu; Lin Shan Shi; Xue Yan Yang; Yong Hong Meng; Xiao Yu Wang; Tian Gong; Yu Rong Guo (Food Chemistry, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Synergistic effect of El Niño Southern oscillation and subtropical Indian Ocean Dipole on Southern China winter precipitation - Bicheng Huang; Tao Su; Rong Zhi; Zengping Zhang; Hongyan Shen; Yongping Wu; Taichen Feng (Atmospheric Research, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Relationship between daily variations of methane emissions and eructation peaks in dairy cows measured with an automated head-chamber system - Rong Wang; Yu Rong Cao; Xiu Min Zhang; Fan Zhang; Xu Tian; Rong Zhen Zhong; Zhi Liang Tan; Min Wang (Animal Feed Science and Technology, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

A new δ-valerolactone produced by marine Streptomyces sp. YIM 13591 - Bing Zhang; Yu-ying Zhao; Zhi-pu Huang; Ke-tao Zhang; Xiao-rong Xu; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2023)

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Amorphous biomineral-reinforced hydrogels with dramatically enhanced toughness for strain sensing - Jia-hua Liu; Zhengyi Mao; Yuhan Chen; Yunchen Long; Haikun Wu; Junda Shen; Rong Zhang; Oscar W.H. Yeung; Binbin Zhou; Chunyi Zhi; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2023)

Asymmetry of Salinity Variability in the Tropical Pacific during Interdecadal Pacific Oscillation Phases - Hai Zhi; Zihui Yang; Rong-Hua Zhang; Pengfei Lin; Jifeng Qi; Yu Huang; Meng Dong (Advances in Atmospheric Sciences, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Molecular Hydrogen Mediates Neurorestorative Effects After Stroke in Diabetic Rats: the TLR4/NF-κB Inflammatory Pathway - Wan-Chao Yang; Ting-ting Li; Qiang Wan; Xin Zhang; Li-Ying Sun; Yu-Rong Zhang; Pei-Chen Lai; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)
Diabetes is an independent risk factor for stroke and amplifies inflammation. Diabetic stroke is associated with a higher risk of death and worse neural function. The identification of effective anti-inflammatory molecules with translational advantages is particularly important to promote perioperative neurorestorative effects. Applying molecular hydrogen, we measured blood glucose levels before and after middle cerebral artery occlusion (MCAO), 48-h cerebral oedema and infarct volumes, as well as 28-day weight, survival and neurological function. We also measured the levels of TLR4, NF-κB p65, phosphorylated NF-κB p65, catecholamines, acetylcholine and inflammatory factors. All measurements comprehensively showed the positive effect and translational advantage of molecular hydrogen on diabetic stroke. Molecular hydrogen improved the weight, survival and long-term neurological function of rats with diabetic stroke and alleviated changes in blood glucose levels before and after middle cerebral artery occlusion (MCAO), but no difference in circadian rhythm was observed. Molecular hydrogen inhibited the phosphorylation of NF-κB and significantly reduced inflammation. Molecular hydrogen mediates neurorestorative effects after stroke in diabetic rats. The effect is independent of circadian rhythms, indicating translational advantages. The molecular mechanism is related to the TLR4/NF-κB pathway and inflammation. Graphical abstract Molecular hydrogen (H 2 ) affects outcomes of ischemic stroke with diabetes mellitus (DM).

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

The loss of Halloween gene function seriously affects the development and reproduction of Diaphorina citri (Hemiptera: Liviidae) and increases its susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Jing Wang; Tian-Rong Xin; Zhi-Wen Zou; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Chemical constituents from the root bark of Morus alba and their chemotaxonomic significance - Xiao-Cong Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

Salinity interdecadal variability in the western equatorial Pacific and its effects during 1950–2018 - Rong-Hua Zhang; Guanghui Zhou; Hai Zhi; Chuan Gao; Hongna Wang; Licheng Feng (Climate Dynamics, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Spinal cord astrocyte P2X7Rs mediate the inhibitory effect of electroacupuncture on visceral hypersensitivity of rat with irritable bowel syndrome - Zhi-jun Weng; Shi-xiu Hu; Fang Zhang; Zhi-ying Zhang; Yun Zhou; Min Zhao; Yan Huang; Yu-hu Xin; Huan-gan Wu; Hui-rong Liu (Purinergic Signalling, 2023)

Origin of clay in granite intrusive contact zone and its influence on tunnel deformation and instability - Guo-Hua Zhang; Bo-Wen Zhang; Fei Tan; Zhong-Hou Liu; Jun-Peng Zou; Zhong-Zhi Xie; Jin-Quan Wu; Zhi-Ping Lin; Zhan-Rong Zhang (Engineering Geology, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Variations in July extreme precipitation in Henan Province and the related mechanisms - Ma Qianrong; Hu Rui; Wu Yongping; Zhang Jie; Zhi Rong; Feng Guoling (International Journal of Climatology, 2022)
Extreme precipitation in July across Henan Province and the possible mechanisms involved were investigated. The precipitation in Henan reaches its maximum in July. During 1979–2021, the precipitation in July changed weakly, but the intensity (R99p) and frequency (R99f) of extreme precipitation showed certain increasing trends, with a significant increase in northern Henan. The proportion of extreme precipitation in total precipitation exhibited a significant upward trend. Wavelet analysis results showed that the extreme precipitation in Henan mainly has a 2–3‐year periodicity, and remarkable interannual variation. Furthermore, nearly 80% of the July extreme precipitation events within the magnitude of 50–100 mm occurred 2–3 times. The first two empirical orthogonal function modes of July R99p exhibited a quasi‐monopole pattern (EOF1) and meridional dipole pattern (EOF2), respectively. Further analysis revealed that EOF1 and EOF2 were related to the Silk Road teleconnection pattern (SRP) and the East Asia/Pacific teleconnection pattern (EAP). Circulation factors influenced the interannual variation of R99p, especially in recent years. Furthermore, the associated sea surface temperature anomalies over the Western Pacific and Indian Ocean can intensify the eastward extension of the South Asian high and westward strengthening of the western Pacific subtropical high, which further impacted the SRP and EAP pattern and enhanced the increment of extreme precipitation in Henan Province.

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Plastid diversity and chromoplast biogenesis in differently coloured carrots: role of the DcOR3Leu gene - Yu-Min Zhang; Rong-Hua Wu; Lu Wang; Ya-Hui Wang; Hui Liu; Ai-Sheng Xiong; Zhi-Sheng Xu (Planta, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Phosphorylation of Truncated Tau Promotes Abnormal Native Tau Pathology and Neurodegeneration - Longfei Li; Yanli Jiang; Gang Wu; Yacoubou Abdoul Razak Mahaman; Dan Ke; Qun Wang; Bin Zhang; Jian-Zhi Wang; Hong-Lian Li; Rong Liu; Xiaochuan Wang (Molecular Neurobiology, 2022)

Analysis of the atmospheric direct dynamic source for the westerly extended WPSH and record-breaking Plum Rain in 2020 - Yuheng Zhao; Jianbo Cheng; Guolin Feng; Rong Zhi; Zhihai Zheng; Zengping Zhang (Climate Dynamics, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Quinolizidine alkaloids from the roots of Sophora flavescens - Jian-Chun Li; Zhi-Jun Zhang; Dan Liu; Ming-Yan Jiang; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2022)

Reasonable application range of flocculation–solidification combined method in treatment of hydraulically dredged mud slurry - Rong-Jun Zhang; Zhi-Hao Xu; Jun-Jie Zheng; Lin-Wei Tu; Zhan-fang Huang (Marine Georesources & Geotechnology, 2022)

Sediment Resuspension as a Major Contributor to Sinking Particles in the Northwestern South China Sea: Evidence From Observations and Modeling - Lihua Ran; Wentao Ma; Martin G. Wiesner; Yuntao Wang; Jianfang Chen; Lanlan Zhang; Zhi Yang; Jingjing Zhang; Hongliang Li; Jian Ren; Rong Xiang; Erick Fredj (Frontiers in Marine Science, 2022)
The lateral advection of sinking particles is a well-known phenomenon in the South China Sea (SCS) and has a significant impact on the estimation of the efficiency of the biological carbon pump. However, little is known about the sources and pathways of sinking particles. Here, we present benthic and freshwater diatom fluxes and relative abundances collected by a sediment trap deployed at a water depth of 1,000 m and more than 500 m above the seafloor in the northwestern SCS, indicating that laterally transported resuspended sediment accounts for a significant part of the particle flux to the deep sea. A Lagrangian particle tracking model (LPTM) revealed that the resuspended particles likely originated from the neighboring continental slope, approximately 12–145 km to the west of the study site. Sediment trap observations and the LPTM together indicated that the impact of resuspended sediment occurred mainly in the deep water, and especially strong sediment resuspension was related to summer monsoon-induced coastal upwelling. The results suggest that particle resuspension has an important impact on the biological pump as well as on paleoenvironmental reconstructions of the SCS.

Correction to: A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Sea surface salinity-derived indexes for distinguishing two types of El Niño events in the tropical Pacific - Hai Zhi; Pengfei Lin; Zhujun Fang; Hailong Liu; Rong-Hua Zhang; Wenrong Bai (Science China Earth Sciences, 2021)

Hippocampal Interneurons are Required for Trace Eyeblink Conditioning in Mice - Wei-Wei Zhang; Rong-Rong Li; Jie Zhang; Jie Yan; Qian-Hui Zhang; Zhi-An Hu; Bo Hu; Zhong-Xiang Yao; Hao Chen (Neuroscience Bulletin, 2021)
While the hippocampus has been implicated in supporting the association among time-separated events, the underlying cellular mechanisms have not been fully clarified. Here, we combined in vivo multi-channel recording and optogenetics to investigate the activity of hippocampal interneurons in freely-moving mice performing a trace eyeblink conditioning (tEBC) task. We found that the hippocampal interneurons exhibited conditioned stimulus (CS)-evoked sustained activity, which predicted the performance of conditioned eyeblink responses (CRs) in the early acquisition of the tEBC. Consistent with this, greater proportions of hippocampal pyramidal cells showed CS-evoked decreased activity in the early acquisition of the tEBC. Moreover, optogenetic suppression of the sustained activity in hippocampal interneurons severely impaired acquisition of the tEBC. In contrast, suppression of the sustained activity of hippocampal interneurons had no effect on the performance of well-learned CRs. Our findings highlight the role of hippocampal interneurons in the tEBC, and point to a potential cellular mechanism subserving associative learning.

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Triaxial Compression Testing at Constant and Reducing Confining Pressure for the Mechanical Characterization of a Specific Type of Sandstone - Jiu-chang Zhang; Zhi-nan Lin; Bo Dong; Rong-xin Guo (Rock Mechanics and Rock Engineering, 2021)

A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Knockdown of Arginyl-tRNA Synthetase Attenuates Ischemia-Induced Cerebral Cortex Injury in Rats After Middle Cerebral Artery Occlusion - Yang Liu; Xue-Bin Hu; Li-Zhi Zhang; Zi Wang; Rong Fu (Translational Stroke Research, 2021)
Some researchers have previously shown that RNAi knockdown of arginyl-tRNA synthetase (ArgRS) before or after a hypoxic injury can rescue animals from death, based on the model organism, C. elegans . However, there has been no study on the application of arginyl-tRNA synthetase knockdown in treating mammalian ischemic stroke, and its potential mechanism and effect on ischemic brain damage are still unknown. Here, we focused on the Rars gene, which encodes an arginyl-tRNA synthetase, and examined the effects of Rars knockdown in a permanent middle cerebral artery occlusion model in rats. To achieve this aim, adult male Sprague-Dawley (SD) rats were given right cerebral cortex injections of short hairpin RNA (shRNA) adenovirus (AV) particles to knock down arginyl-tRNA synthetase, and a non-targeting control (NTC) vector or phosphate-buffered solution served as the controls. After 4 days, the rats were exposed to permanent middle cerebral artery occlusion (pMCAO). Then, the right cerebral cortex level of arginyl-tRNA synthetase was examined, and the effects of the Rars knockdown were evaluated by differences in infarction volume, oxidative stress, blood-brain barrier, mitochondrial function, and glucose metabolism at 1 day and 3 days after MCAO. The injection of shRNA adenovirus particles successfully suppressed the expression of arginyl-tRNA synthetase in the cerebral cortex. We observed an improvement in oxidative stress, mitochondrial function, and glucose utilization and a reduction in brain edema compared with the non-targeting control rats with suppressed expression of arginyl-tRNA synthetase mRNA in the ipsilateral ischemic cortex of the brain. Our findings indicate that knockdown of arginyl-tRNA synthetase in the cerebral cortex exerted neuroprotective effects, which were achieved not only by the improvement of oxidative stress and glucose utilization but also by the maintenance of mitochondrial morphological integrity and the preservation of mitochondrial function. Knockdown of ArgRS administration could be a promising approach to protect ischemic stroke.

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Correlation of exosomal microRNA clusters with bone metastasis in non-small cell lung cancer - Xiao-Rong Yang; Can Pi; Ruoying Yu; Xiao-Jun Fan; Xiao-Xiao Peng; Xu-Chao Zhang; Zhi-Hong Chen; Xue Wu; Yang Shao; Yi-Long Wu; Qing Zhou (Clinical & Experimental Metastasis, 2021)
20–40% of lung cancer patients develop bone metastasis (BM) with significantly decreased overall survival. Currently, BM is mainly diagnosed by computerized tomography (CT) scan or magnetic resonance imaging (MRI) when symptom develops. Novel biomarkers with higher prediction value of BM are needed. Plasma-derived exosomal microRNAs had been isolated and sequenced of total 30 non-small cell lung cancer (NSCLC) patients including 16 with bone metastasis and 14 without bone metastasis. Hierarchical clustering based on the total miRNA profile can clearly separate cancer patients and healthy individuals (H), but not patients with (BM +) or without (BM−) BM. Weight Co-expression network of miRNAs (WGCNA) analyses identified three consensus clusters (A, B, C) of highly correlated miRNAs, among which cluster B (144 miRNAs) showed significantly differential expression in lung cancer patients, especially in BM + group. Pathway analysis of cluster B miRNAs revealed enrichment in metabolic pathways that may involve in preconditioning of the metastatic niche. Three differentially expressed miRNAs between BM + and BM− patients within cluster B were identified as miR-574-5p, a suppressor of Wnt/β-catenin pathway, was down-regulated, while miR-328-3p and miR-423-3p, two activators of the same pathway, were up-regulated in BM + patients. Cluster A miRNAs (n = 49) also showed trend of upregulation in BM + patients. Interestingly, pathway analysis indicated that 43 of them are associated with chromosome14, which has been suggested to promote epithelial-mesenchymal transition (EMT) and bone metastasis.

Infestation and distribution of gamasid mites on Himalayan field rat (Rattus nitidus) in Yunnan Province of Southwest China - Rong Xiang; Xian-Guo Guo; Cheng-Fu Zhao; Rong Fan; Ke-Yu Mao; Zhi-Wei Zhang; Xiao-Bin Huang (Biologia, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Ecological analysis of gamasid mites on the body surface of Norway rats (Rattus norvegicus) in Yunnan Province, Southwest China - Zhe Liu; Xian-Guo Guo; Rong Fan; Cheng-Fu Zhao; Ke-Yu Mao; Zhi-Wei Zhang; Yue Zhao (Biologia, 2020)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

High resolution UPLC-MS/MS method for simultaneous separation and determination of six flavonoids from semen cuscutae extract in rat plasma: application to comparative pharmacokinetic studies in normal and kidney-deficient rats - Wei Zhang; Zhi-Tian Fu; Yao Xie; Zhi-Wen Duan; Yu Wang; Rong-Hua Fan (Natural Product Research, 2020)

Transcript profiling of genes involved in carotenoid biosynthesis among three carrot cultivars with various taproot colors - Ya-Hui Wang; Tong Li; Rong-Rong Zhang; Ahmed Khadr; Yong-Sheng Tian; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Steroidogenic acute regulatory protein/aldosterone synthase mediates angiotensin II-induced cardiac fibrosis and hypertrophy - Wei-Wei Zhang; Rong-Hua Zheng; Feng Bai; Katelyn Sturdivant; Ning-Ping Wang; Erskine A. James; Himangshu S. Bose; Zhi-Qing Zhao (Molecular Biology Reports, 2020)

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Impact of CYP2R1, CYP27A1 and CYP27B1 genetic polymorphisms controlling vitamin D metabolism on susceptibility to hepatitis C virus infection in a high-risk Chinese population - Jing-jing Yang; Hao-zhi Fan; Ting Tian; Meng-ping Wu; Chao-nan Xie; Peng Huang; Rong-bin Yu; Hong-Gang Yi; Yun Zhang; Jie Wang (Archives of Virology, 2019)

Observed structural relationships between ocean chlorophyll variability and its heating effects on the ENSO - Rong-Hua Zhang; Feng Tian; Hai Zhi; Xianbiao Kang (Climate Dynamics, 2019)

Identification and Phylogenetic Analysis of Xanthomonas albilineans (Ashby) Dowson Based on Multiple Gene Sequences in Yunnan Province, China - Rong-Yue Zhang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Wen-Feng Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin; Ying-Kun Huang (Sugar Tech, 2019)

Molecular Identification of Sugarcane White Leaf in Puer, Yunnan Province, China - Rong-Yue Zhang; Wen-Feng Li; Ying-Kun Huang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Sugar Tech, 2019)

Developing genetically segregating populations for localization of novel sugarcane brown rust resistance genes - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Hong-Li Shan; Rong-Yue Zhang; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Euphytica, 2019)

Salinity effects on the 2014 warm “Blob” in the Northeast Pacific - Hai Zhi; Pengfei Lin; Rong-Hua Zhang; Fei Chai; Hailong Liu (Acta Oceanologica Sinica, 2019)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

QTL analysis of delayed maize flowering in response to low phosphate across multi-environments - Zhiyong Ren; Xiao Zhang; Hailan Liu; Wenjun Liu; Zhi Nie; Dan Liu; Ling Wu; Haijian Lin; Shunzong Su; Duojiang Gao; Bowen Luo; Peng Ma; et al. (Euphytica, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Field Resistance of Different Sugarcane Varieties to Sugarcane Thrips (Fulmekiola serratus) in China - Zhi-Ming Luo; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Jie Li; Jiong Yin (Sugar Tech, 2019)

Calcium intake and colon cancer risk subtypes by tumor molecular characteristics - NaNa Keum; Li Liu; Tsuyoshi Hamada; Zhi Rong Qian; Jonathan A. Nowak; Yin Cao; Annacarolina da Silva; Keisuke Kosumi; Mingyang Song; Daniel Nevo; Molin Wang; Andrew T. Chan; et al. (Cancer Causes & Control, 2019)

A Density-Changing Centrifugation Method for Efficient Separation of Free Drugs from Drug-Loaded Particulate Delivery Systems - Lu Han; Hongyan Zhan; Xun Sun; Zhi-Rong Zhang; Li Deng (The AAPS Journal, 2019)

Interannual Salinity Variability in the Tropical Pacific in CMIP5 Simulations - Hai Zhi; Rong-Hua Zhang; Pengfei Lin; Peng Yu (Advances in Atmospheric Sciences, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Correction to: Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji‑Dong Ya; Zhi‑Xiang Yu; Yong-Qiong Yang; Shu‑Dong Zhang; Zhi‑Rong Zhang; Jie Cai; Jun‑Bo Yang; Wen‑Bin Yu (Conservation Genetics Resources, 2018)

Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji-Dong Ya; Zhi-Xiang Yu; Yan-Qiong Yang; Shu-Dong Zhang; Zhi-Rong Zhang; Jie Cai; Jun-Bo Yang; Wen-Bin Yu (Conservation Genetics Resources, 2018)

Hydrological response of biological soil crusts to global warming: A ten‐year simulative study - Xin‐Rong Li; Rong‐Liang Jia; Zhi‐Shan Zhang; Peng Zhang; Rong Hui (Global Change Biology, 2018)
Biological soil crusts across the desert regions play a key role in regional ecological security and ecological health. They are vital biotic components of desert ecosystems that maintain soil stability, fix carbon and nitrogen, influence the establishment of vascular plants, and serve as habitats for a large number of arthropods and microorganisms, as well as influencing soil hydrological processes. Changes in temperature and precipitation are expected to influence the functioning of desert ecosystems by altering biotic components such as the species composition of biological soil crusts. However, it remains unclear how these important components will respond to the prolonged warming and reduced precipitation that is predicted to occur with climate change. To evaluate how the hydrological properties of these biological soil crusts respond to these alterations, we used open‐top chambers over a 10‐year period to simulate warming and reduced precipitation. Infiltration, dew entrapment, and evaporation were measured as surrogates of the hydrological functioning of biological soil crusts. It was found that the ongoing warming coupled with reduced precipitation will more strongly affect moss in crustal communities than lichens and cyanobacteria, which will lead to a direct alteration of the hydrological performance of biological soil crusts. Reductions in moss abundance, surface cover, and biomass resulted in a change in structure and function of crustal communities, decreased dew entrapment, and increased infiltration and evaporation of biological soil crusts in desert ecosystems, which further impacted on the desert soil water balance.

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

Design, synthesis and biological evaluation of novel furoxan-based coumarin derivatives as antitumor agents - Zhuo Zhang; Zhi-Wei Bai; Yong Ling; Li-Qin He; Peng Huang; Hong-Xia Gu; Rong-Feng Hu (Medicinal Chemistry Research, 2018)

Molecular detection and phylogenetic analysis of viruses causing mosaic symptoms in new sugarcane varieties in China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (European Journal of Plant Pathology, 2017)

Effect of Co-overexpression of Nisin Key Genes on Nisin Production Improvement in Lactococcus lactis LS01 - Zhi-Jian Ni; Xiao-yuan Zhang; Fei Liu; Miao Wang; Rong-hua Hao; Pei-xue Ling; Xi-Qiang Zhu (Probiotics and Antimicrobial Proteins, 2017)

Molecular Detection of Bru1 Gene and Identification of Brown Rust Resistance in Chinese Sugarcane Germplasm - Wen-Feng Li; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (Sugar Tech, 2017)

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

Responses of soil inhabiting nitrogen-cycling microbial communities to wetland degradation on the Zoige Plateau, China - Li-sha Wu; Yuan-yang Nie; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

Steroidobacter flavus sp. nov., a microcystin-degrading Gammaproteobacterium isolated from soil - Zhi-Lian Gong; Chang-Feng Zhang; Rong Jin; Yu-Qin Zhang (Antonie van Leeuwenhoek, 2016)

Long-Acting Phospholipid Gel of Exenatide for Long-Term Therapy of Type II Diabetes - Mei Hu; Yu Zhang; Nanxi Xiang; Ying Zhong; Tao Gong; Zhi-Rong Zhang; Yao Fu (Pharmaceutical Research, 2016)

Erratum to: Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Assessment of interannual sea surface salinity variability and its effects on the barrier layer in the equatorial Pacific using BNU-ESM - Hai Zhi; Rong-Hua Zhang; Fei Zheng; Pengfei Lin; Lanning Wang; Peng Yu (Advances in Atmospheric Sciences, 2016)

Age-related changes in photosynthesis and water relations of revegetated Caragana korshinskii in the Tengger desert, Northern China - Jing-Ting Bao; Jin Wang; Xin-Rong Li; Zhi-Shan Zhang; Jie-Qiong Su (Trees, 2015)

Simulation of salinity variability and the related freshwater flux forcing in the tropical Pacific: An evaluation using the Beijing normal university earth system model (BNU-ESM) - Hai Zhi; Rong-Hua Zhang; Pengfei Lin; Lanning Wang (Advances in Atmospheric Sciences, 2015)

Quantitative analysis of the feedback induced by the freshwater flux in the tropical Pacific using CMIP5 - Hai Zhi; Rong-Hua Zhang; Pengfei Lin; Lanning Wang (Advances in Atmospheric Sciences, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

Isolation and characterization of 18 microsatellites for Aconitum vilmorinianum Kom. (Ranunculaceae) using next-generation sequencing technology - Jun He; Zhi-Rong Zhang; Jun-Bo Yang; Hong Wang; Jing Meng (Conservation Genetics Resources, 2015)

Development of high oleic oil crop platform in flax through RNAi-mediated multiple FAD2 gene silencing - Yurong Chen; Xue-Rong Zhou; Zhi-Jun Zhang; Paul Dribnenki; Surinder Singh; Allan Green (Plant Cell Reports, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

Soil cellulase activity and fungal community responses to wetland degradation in the Zoige Plateau, China - Li-sha Wu; Su Feng; Yuan-yang Nie; Jian-hong Zhou; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Auditory sexual difference in the large odorous frog Odorrana graminea - Wei-Rong Liu; Jun-Xian Shen; Yu-Jiao Zhang; Zhi-Min Xu; Zhi Qi; Mao-Qiang Xue (Journal of Comparative Physiology A, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

Effect of a single-dose rifampin on the pharmacokinetics of pitavastatin in healthy volunteers - Yao Chen; Wei Zhang; Wei-hua Huang; Zhi-rong Tan; Yi-cheng Wang; Xi Huang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Genome-Wide Phylogenetic Analysis of Stress-Activated Protein Kinase Genes in Rice (OsSAPKs) and Expression Profiling in Response to Xanthomonas oryzae pv. oryzicola Infection - Mei-Rong Xu; Li-Yu Huang; Fan Zhang; Ling-Hua Zhu; Yong-Li Zhou; Zhi-Kang Li (Plant Molecular Biology Reporter, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Effect of sand-stabilizing shrubs on soil respiration in a temperate desert - Zhi-Shan Zhang; Xin-Rong Li; Robert S. Nowak; Pan Wu; Yan-Hong Gao; Yang Zhao; Lei Huang; Yi-Gang Hu; Rong-Liang Jia (Plant and Soil, 2013)

Nicotianamine synthase gene family as central components in heavy metal and phytohormone response in maize - Mei-Liang Zhou; Lei-Peng Qi; Jun-Feng Pang; Qian Zhang; Zhi Lei; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

The Implantable and Biodegradable PHBHHx 3D Scaffolds Loaded with Protein-Phospholipid Complex for Sustained Delivery of Proteins - Qiang Peng; Yong-Jie Yang; Ting Zhang; Cheng-Yu Wu; Qin Yang; Xun Sun; Tao Gong; Ling Zhang; Zhi-Rong Zhang (Pharmaceutical Research, 2013)

Polymorphisms of UGT1A9 and UGT2B7 influence the pharmacokinetics of mycophenolic acid after a single oral dose in healthy Chinese volunteers - Dong Guo; Liang-Fang Pang; Yang Han; Hong Yang; Guo Wang; Zhi-rong Tan; Wei Zhang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Genotype and haplotype analysis of the AZGP1 gene in cattle - Bao Zhang; Yi Kun Guo; Shengbin Li; Liang Zhi Zhang; Xian Yong Lan; Shen Rong Hu; Hong Chen (Molecular Biology Reports, 2012)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Iodine-125 Seed Implantation in the Treatment of Sacrococcygeal Chordoma: A Case Report - Rong-hui Ni; Ge Wang; Zhi-min Zhang; Jun-gang Ma (Cell Biochemistry and Biophysics, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Solid Lipid Nanoparticles Loaded with Anti-microRNA Oligonucleotides (AMOs) for Suppression of MicroRNA-21 Functions in Human Lung Cancer Cells - San-Jun Shi; Zhi-Rong Zhong; Jie Liu; Zhi-Rong Zhang; Xun Sun; Tao Gong (Pharmaceutical Research, 2012)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Complete genome sequence of a tomato spotted wilt virus isolate from China and comparison to other TSWV isolates of different geographic origin - Zhong-Ze Hu; Zhi-Ke Feng; Zhi-Jun Zhang; Yao-Bin Liu; Xiao-Rong Tao (Archives of Virology, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Cloning and functions analysis of a pyruvate dehydrogenase kinase in Brassica napus - Rong-Jun Li; Zhi-Yong Hu; Hua-Shan Zhang; Gao-Miao Zhan; Han-Zhong Wang; Wei Hua (Plant Cell Reports, 2011)

Inhibition of oestrogen biosynthesis induces mild anxiety in C57BL/6J ovariectomized female mice - Fan-Tao Meng; Rong-Jun Ni; Zhi Zhang; Jun Zhao; Ya-Jing Liu; Jiang-Ning Zhou (Neuroscience Bulletin, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Molecular phylogenetic reconstruction of Osmanthus Lour. (Oleaceae) and related genera based on three chloroplast intergenic spacers - Shi-Quan Guo; Min Xiong; Chun-Feng Ji; Zhi-Rong Zhang; De-Zhu Li; Zhi-Yong Zhang (Plant Systematics and Evolution, 2011)

Dynamics of vegetation and soil carbon and nitrogen accumulation over 26 years under controlled grazing in a desert shrubland - Zhi-Yu Zhou; Feng-Rui Li; Shan-Ke Chen; Hong-Rong Zhang; Guangdi Li (Plant and Soil, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Endophytic fungus Cladosporium cladosporioides LF70 from Huperzia serrata produces Huperzine A - Zhi Bin Zhang; Qing Gui Zeng; Ri Ming Yan; Ya Wang; Zheng Rong Zou; Du Zhu (World Journal of Microbiology and Biotechnology, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Inhalable Microparticles as Carriers for Pulmonary Delivery of Thymopentin-Loaded Solid Lipid Nanoparticles - Yan-Zhen Li; Xun Sun; Tao Gong; Jie Liu; Jiao Zuo; Zhi-Rong Zhang (Pharmaceutical Research, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Differential expression of TRPC channels in the left ventricle of spontaneously hypertensive rats - Fang-fang Liu; Zhi-yong Ma; Duo-ling Li; Jin-bo Feng; Kai Zhang; Rong Wang; Wei Zhang; Li Li; Yun Zhang (Molecular Biology Reports, 2010)

Validity and reliability testing of the Chinese (mainland) version of the 39-item Parkinson’s Disease Questionnaire (PDQ-39) - Wei Luo; Xiao-hong Gui; Bo Wang; Wen-ying Zhang; Zhi-yuan Ouyang; Yi Guo; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

New cyclopentenones from strain Trichoderma sp. YLF-3 - Guo-Hong Li; Li-Jun Zheng; Fang-Fang Liu; Li-Zhi Dang; Lei Li; Rong Huang; Ke-Qin Zhang (Natural Product Research, 2009)

The mixture of procyanidins extracted from the lotus seed pod and bilobalide ameliorates scopolamine-induced memory impairment in mice - Li Zhang; Ji-Qu Xu; Shuang Rong; Bi-Jun Xie; Zhi-Da Sun; Yun-Jian Zhang; Lie-Gang Liu (Neuroscience Bulletin, 2009)

Increased expression of Toll-like receptors 4 and 9 in human lung cancer - Yan-Bei Zhang; Feng-Lian He; Ming Fang; Tian-Feng Hua; Bi-Dan Hu; Zhi-Hong Zhang; Qi Cao; Rong-Yu Liu (Molecular Biology Reports, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

Distribution, biomass, and dynamics of roots in a revegetated stand of Caragana korshinskii in the Tengger Desert, northwestern China - Zhi-Shan Zhang; Xin-Rong Li; Li-Chao Liu; Rong-Liang Jia; Jing-Guang Zhang; Tao Wang (Journal of Plant Research, 2009)

Isolation and characterization of microsatellite markers for the endangered Taxus yunnanensis - Ying-Chun Miao; Jian-Rong Su; Zhi-Jun Zhang; Hui Li; Jing Luo; Ya-Ping Zhang (Conservation Genetics, 2008)

Development of the male reproductive structures in Taxus yunnanensis - Bing-Yi Wang; Jian-Rong Su; Danilo D. Fernando; Zong-Hui Yang; Zhi-Jun Zhang; Xiao-Ming Chen; Yan-Ping Zhang (Plant Systematics and Evolution, 2008)

Sorption of 1,1,1-trichloro-2,2-bis(p-chlorophenyl) ethane (DDT) by clays and organoclays - Rong-Ling Dai; Gang-Ya Zhang; Xiao-Zhi Gu; Ming Kuang Wang (Environmental Geochemistry and Health, 2008)

Effect of siRNA on HSV-1 plaque formation and relative expression levels of UL39 mRNA - Ren Zhe; Zhang Mei-Ying; Kaio Kitazato; Nobuyuki Kobayash; Zhu Qin-Chang; Zhang Pei-Zhuo; Yang Zhi-Rong; Wang Yi-Fei (Archives of Virology, 2008)

Identification and characterization of ten polymorphic microsatellite loci in the red panda Ailurus fulgens - Liang Zhang; Xu Liang; Zhihe Zhang; Fujun Shen; Wenping Zhang; Kun Wei; Zhi Yang; Rong Hou; Bisong Yue; Hiroshi Kamata; Ken Okabayashi; Shigeo Ohba; et al. (Conservation Genetics, 2008)

Characterization of high-yield performance as affected by genotype and environment in rice - Song Chen; Fang-rong Zeng; Zong-zhi Pao; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Persistence and dissipation of synthetic pyrethroid pesticides in red soils from the Yangtze River Delta area - Xiao-zhi Gu; Gang-ya Zhang; Li Chen; Rong-ling Dai; Yuan-chun Yu (Environmental Geochemistry and Health, 2008)

Development and evaluation of immunoassay for zeranol in bovine urine - Yuan Liu; Cun-zhen Zhang; Xiang-yang Yu; Zhi-yong Zhang; Xiao Zhang; Rong-rong Liu; Xian-jin Liu; Zhen-ming Gong (Journal of Zhejiang University-SCIENCE B, 2007)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Assembly of Plasmid DNA into Liposomes After Condensation by Cationic Lipid in Anionic Detergent Solution - Hong-Wei Zhang; Ling Zhang; Xun Sun; Shu Diao; Zhi-Rong Zhang (Biotechnology Letters, 2005)

Ile118Val genetic polymorphism of CYP3A4 and its effects on lipid-lowering efficacy of simvastatin in Chinese hyperlipidemic patients - An Wang; Bang-Ning Yu; Chen-Hui Luo; Zhi-Rong Tan; Gan Zhou; Lian-Sheng Wang; Wei Zhang; Zhi Li; Jie Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2005)

Genetic analysis and breeding use of blast resistance in a japonica rice mutant R917 - Ming Xian Zhang; Jian Long Xu; Rong Ting Luo; De Shi; Zhi Kang Li (Euphytica, 2003)